KNOWLEDGE, ATTITUDE AND PRACTICES AMONG MEDICAL STUDENTS REGARDING ACNE - Mohan Lal, Deepa; Mansoor, Maria; Amin, Emaan; Memon, Mohammad Mustafa; Khan, Maaz Shah; Talat, Humaira; Mirza, Reema; Wahid, Zarnaz (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To investigate knowledge, attitudes, practices, and quality of life of patients with acne. METHODOLOGY: This observational cross-sectional study was done from May to June 2018 at Dow University of Health Sciences, Karachi after obtaining an institution board review approval. After Verbal consent, data were collected using convenience sampling via validated questionnaire survey forms obtained from each participant. Analysis was performed employing Statistical Analysis for Social Science (SPSS) v. 23.0. RESULTS: The study participants had a mean age of 21±2 years. Around three-fourths of the study population (n=315,76%) had a good knowledge score involving aggravating and relieving factors of acne. The age of the study population and their knowledge score did have a significant association between them (p=0.141) but there was a significant correlation between the sex (p=0.006) and a positive family history of acne (p=0.00) knowledge score. More than half of the study population (n=230, 55%) reported that they feel depressed when they have acne. Regarding attitude and practices, few participants used over-the-counter topical creams (n=78,19%) for prevention, and less than half (n=189,46%) sought acne treatment. Furthermore, the mean CADI score was 3.6±2.8. CONCLUSION: Despite satisfactory knowledge, patients showed poor attitudes and practices. However, there exist various misconceptions regarding the disease among patients. Dermatologists should keep in mind the impairment in the quality of life of patients when constructing a management plan. KEYWORDS: Knowledge, Attitude, Practices, Medical students, Acne